ANALISIS FAKTOR INTRINSIK DAN EKSTRINSIK YANG BERPENGARUH TERHADAP INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA TAHUN 2013 - Yuli Trisnawati; Kuswatin Khasanah Akademi Kebidanan YLPP Purwokerto (Jurnal Kebidanan, 2013)
ANALISIS FAKTOR INTRINSIK DAN EKSTRINSIK YANG BERPENGARUH TERHADAP INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA TAHUN 2013 Yuli Trisnawati & Kuswatin Khasanah Akademi Kebidanan YLPP Purwokerto ABSTRACT ARI was the most important cause of morbidity and mortality to children. ARI case was placed in the first level in the most care in Indonesia. It showed illness number because or ARI was still high. The amount of children who suffered ARI from January up to march 2013 in Tumanggal village was 52 of 234 children. The objective of this research was to show several determinant which were related to ARI to children under five in Tumanggal Village Pengadegan Sub District Purbalingga Regency Year 2013. This research was an analytic survey research by case control approaching. The sample was 92 and taken by using systematic random sampling. The instruments used were observation sheet and interview. Data analysis was done by using chi square. The result showed that there was relation between the house condition and ARI (chi square p value = 0,034 < 0,05, OR: 1,719), there wasn’t relation between nutrition status and ARI (chi square p value = 0,420 > 0,05), and there was relation between family smoking habit at home and ARI (chi square p value = 0,043 < 0,05, OR: 2.917). And the family smoking habit is the most faktor that influence ARI wit OR : 0.320 and p 0.040. Conclution there was a relation between the house condition and family smoking habit at home to ARI but there wasn’t relation between nutrition status and ARI to the children under five years. And the family smoking habit is the most faktor that influence ARI to children under five years. Key words : ARI, house condition, nutrition status, smoking